Efeitos de diferentes frações inspiradas de oxigênio sobre variáveis cardiorrespiratórias e histopatologia pulmonar em coelhos com cardiomiopatia dilatada, anestesiados com sevofluorano - Gering, Ana Paula [UNESP] (2015)
The respiratory, cardiovascular and blood gas effects as well as histopathological changes of the lung parenchyma after providing two inspired oxygen concentrations (100 and 60%) were evaluated in rabbits with dilated cardiomyopathy induced by doxorubicin and anesthetized with sevoflurane. Fourteen adult rabbits, male and female, were used. For that, they were equally divided into two groups, G100 and G60, and induced to anesthesia with sevoflurane, by naso-oral mask forbidden to 2.5 MAC, diluted in total flow of 1 L/min of oxygen at 100 %. After intubation with a Maggil tracheal probe, the inhalational anesthesia with sevoflurane at 1.0 MAC was instituted. The oxygen concentration was at 100% for G100 and adjusted by 60% for G60. After 30 minutes from the anesthetic induction, the first harvest data was collected and named (M0). New measurements were performed after 15 minutes (M15) and subsequently at intervals of 15 minutes over a period of 60 minutes (M30, M45, and M60). At the end, the animals were euthanised and lung fragments samples were collected for further histopathological analysis. The numerical data were submitted to analysis of variance of one and two lives followed by Bonferroni test, considering the significance level of p ≤ 0.05. Though, for the histopathology scores, the percentage of total changes observed in each group was considered. From the respiratory parameters, we noticed a difference between the groups at all times, for alveolar oxygen pressure (PAO2), in the alveolar-arterial oxygen difference [P (A - a) O2] with G100 values considerably higher than the G60, and at M60 the difference between PaCO2 and ETCO2 with G100 also presented higher values than G60. The cardiovascular dynamics showed difference at M0 with G100, demonstrating higher average than the G60. From the blood gas parameters, the arterial oxygen tension (PaO 2) showed higher values in G100 when compared to G60, at all times. The animals ...